Counseling to Increase Legal Literacy About Early Marriage in Pocangan Village, Sukowono District, Jember Regency - St. Sariroh; Moh. Ali; Ibnu Alwaton Surya Waliden (Indonesian Journal Publisher, 2024)
Early marriage has become a tradition in village communities. As happened in Jember Regency, in 2023 there will be approximately 905 of early marriage cases. Even though Law No. 16 of 2019 regulates that the minimum age limit for men and women to marry is 19 years. Apart from traditional factors, many other factors cause early marriage, such as promiscuity, economic factors, and also the lack of legal literacy in society regarding the age limit for marriage. Therefore, we are conducting counselling to increase legal literacy regarding early marriage in Pocangan Village, Jember Regency to reduce and prevent early marriage cases. The method used in this activity is Asset Based Community Development (ABCD), From all stages of service, it was successful in improving public literacy and understanding of marriage laws including age limits for marriage, as well as public awareness to comply with regulations, as well as being able to prevent early marriage and provide positive education to other communities. However, in terms of awareness regarding continuing education, the level of education is still low. Because there is no social or institutional support for continuing school.